Influência da incorporação de resíduo de calcário em um compósito de matriz polimérica isoftálica: obtenção e caracterização - SILVA, Willian Rayol da (2023)
Just as the production demand of industries is constantly growing, the generation of waste in nature grows gradually. Thus, environmental laws were created to protect the environment from possible damage caused by these residues. Thus, composite materials that use industrial waste emerge as an alternative in potential improvement in aiding this disposal. In this work, polymeric matrix composite materials were produced using calcitic limestone waste, with a granulometry of 100 mesh. The manual manufacturing method “hand lay-up” was used, with variations in the proportions, 10%, 20% and 30%. For the matrix phase, the isophthalic polymeric resin was applied, with the addition of 1% of initiator in v/v and 1.5% of activator v/v. The morphological tests were carried out in order to correlate the fracture aspects with the mechanical properties of the specimens. Mineralogical analysis was performed using X-Ray Diffraction and X-Ray Fluorescence. After the initial stages of making the test specimens, physical tests (ASTM D 570, ASTM D 2734 and ASTM D 792), mechanical tests of traction (ASTM D 3039) and flexion (ASTM D 790), fracture analysis performed by Scanning Electron Microscope (SEM) and horizontal flammability (ASTM D 635).Mineralogical analysis was performed using X-Ray Diffraction. After the initial stages of making the specimens, the physical (ASTM D 570, ASTM D 2734 and ASTM D 792) and mechanical tests of traction (ASTM D 3039) and bending (ASTM D 790) were carried out, with fracture analysis performed by Scanning Electron Microscope (SEM). The flame propagation rate was analyzed using the horizontal flammability test (ASTM D 635). The physical tests of the specimens followed the expected pattern for adding the aggregated material to the matrix. The mechanical test obtained satisfactory results that match the initial expectation, increasing its resistance by adding limestone. The fracture test showed good distribution of limestone residue to the matrix and the main failure mechanisms. Regarding flame resistance, the test specimens obtained satisfactory results in all mass fractions, especially when compared to the base standards. In view of all the tests carried out and the proposed analysis, the composite with calcitic limestone can be a technological alternative to minimize socio-environmental impacts, requiring additional tests.